Transcutaneous vagus nerve stimulation: a new strategy for Alzheimer’s disease intervention through the brain-gut-microbiota axis? - Yan, Long; Li, Hong; Qian, Yulin; Zhang, Junfeng; Cong, Shan; Zhang, Xuemin; Wu, Linna; Wang, Yu; Wang, Meng; Yu, Tao (Frontiers in Aging Neuroscience, 2024)
Transcutaneous vagus nerve stimulation (tVNS) is an emerging non-invasive technique designed to stimulate branches of the vagus nerve distributed over the body surface. Studies suggest a correlation between the brain-gut-microbiota (BGM) axis and the pathogenesis of Alzheimer’s disease (AD). The BGM axis represents a complex bidirectional communication system, with the vagus nerve being a crucial component. Therefore, non-invasive electrical stimulation of the vagus nerve might have the potential to modify—most of the time probably in a non-physiological way—the signal transmission within the BGM axis, potentially influencing the progression or symptoms of AD. This review explores the interaction between percutaneous vagus nerve stimulation and the BGM axis, emphasizing its potential effects on AD. It examines various aspects, such as specific brain regions, gut microbiota composition, maintenance of intestinal environmental homeostasis, inflammatory responses, brain plasticity, and hypothalamic–pituitary–adrenal (HPA) axis regulation. The review suggests that tVNS could serve as an effective strategy to modulate the BGM axis and potentially intervene in the progression or treatment of Alzheimer’s disease in the future.